(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the implementation of green technology programs and projects with a focus on Uzbekistan and the broader Central Asian context. The study systematizes regulatory measures, investment mechanisms, renewable energy projects, and institutional barriers that influence the pace of green transformation. Based on a qualitative review of policy documents and a comparative assessment of selected projects, the paper shows that recent reforms have strengthened the legal and strategic basis for renewable energy deployment, energy efficiency, and decarbonization. At the same time, the analysis demonstrates that the effectiveness of green transition depends not only on formal strategies, but also on technology transfer, financing depth, managerial capacity, and workforce skills. The article proposes an analytical scheme for understanding the chain from regulatory design to socio-economic outcomes and argues that green technologies should be treated as a core driver of industrial competitiveness, energy security, and environmental resilience.